Measuring preferences for competition with experimentally-validated survey questions - Francesco Fallucchi; Daniele Nosenzo; Ernesto Reuben (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
We validate experimentally a new survey item to measure the preference for competition. The item, which measures participants' agreement with the statement "Competition brings the best out of me", predicts individuals' willingness to compete in the laboratory after controlling for their ability, beliefs, and risk attitude (Niederle and Vesterlund, 2007). We further validate the explanatory power of our survey item outside of the laboratory, by comparing responses across two samples with predicted differences in their preference for competition: professional athletes and non-athletes. As predicted, we find that athletes score higher on the item than non-athletes.
Keywords: C91; D90; D91; 330; competition; survey question; experiment validation